KEPUTUSAN PETANI TERHADAP MIX PLANTING TANAMAN JENGKOL PADA LAHAN TANAMAN KARET - saputra, Median; Fariadi, Herri; Nurmalia, Ana; Afriani, Ririn (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
The decline in the selling price of rubber caused farmers to mix jengkol planting on rubber plantations, with the aim of increasing land productivity and double profits for farmers. This study aims to determine farmers' decisions and the factors that influence farmers' decisions to plant jengkol on rubber plantations. The method used is descriptive quantitative analysis using a Likert scale, and to determine the factors that influence farmer decisions, multiple linear regression analysis is used. The results showed that the level of decision making by farmers in Ilir Talo Village, Seluma Regency was 35.23 with a very high category. The variable of farmer motivation (X1), and the proximity of farmers to farmer groups and PPL (X2) affect farmers' decisions. While the variables of farmers' involvement in traditional party activities (X3), land ownership (X4), farmers' land area (X5), income (X6) did not affect the decision to plant jengkol plants on rubber plantations in Ilir Talo District, Seluma Regency.